Znaczenie terapii logopedycznej w kształceniu kaznodziejów - Szewczyk, Leszek (Logopedia Silesiana, 2012)
Importance of speech therapy in preachers’ training Characteristics of the preaching of the Church lies in a clearly specified content, quite different from other public speeches, which is the Word of God. This form of preaching, in terms of the content being the Word of God, and in terms of the form being the word of man, can be described as the word of God in the word of man. Therefore efficiency of the Word of God depends in a sense on its human and linguistic sense. A preacher’s word spoken from behind a pulpit should be very powerful. A correct emission is necessary for a beautiful liturgy, but also for a didactic work and preaching. The article, referring to the theory of preaching, point at the importance of a speech therapy in future preachers’ training.